Use of Digital Badges to Recognize Nurse Practitioner Students’ Clinical Skills: A Pilot Project - Huang, Kun (My University, 2023)
Students in nurse practitioner programs are required to learn many clinical skills and procedures. Digital badges were chosen as ways to recognize clinical skills and provide students with means to represent their clinical skill validation on their resumes. The university/project site offers four immersion experiences. Different clinical skills and procedures were taught during the first three immersion experiences. During the fourth immersion, faculty validated students’ skills and awarded them digital badges. A post-survey was conducted to aggregate students’ opinions on receiving the badges. A total of eight badges were created. The overall response rate was 94% for the post-award survey. Over 80% of NP students believed the badges would be a meaningful addition to their resumes and a quick way for future potential employers to see their clinical skills. Faculty in the nursing college played essential roles in the processes of skills validation and awarding badges. The author strongly recommends using digital badges to recognize students’ clinical skills in higher education. There are many opportunities for further exploration to expand the utilization of digital badges. The project’s limitations included the small sample size and the lack of a survey to gather potential employers’ opinions toward the utilization of digital badges.
Keywords: micro-credentialing, digital badges, nurse practitioner students, clinical skills